Soil organic C affected by dry‐season management of no‐till soybean crop rotations in the tropics - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Calonego, Juliano Carlos [UNESP]; Capuani, Silvia [UNESP]; Franzluebbers, Alan J. (Springer Nature, 2021)
Aims: Cover crop species selection for soybean (Glycine max) production under no-tillage (NT) management may affect soil organic C sequestration by altering the quantity and quality of C inputs, thereby affecting cropping system sustainability. If so, the underlying mechanisms for such regulation are still unclear. Methods: We assessed changes in soil C and N fractions at 0-0.1 m depth and soil C stock at 0-0.6 m depth during the last three years of dry-season cover cropping in a soybean production system managed with NT for 9 years on a Rhodic Hapludox in Sao Paulo, Brazil. Dry-season management treatments were repeated yearly in a split-plot scheme. Main plots during the fall-winter were (1) ruzigrass (Urochloa ruziziensis), (2) grain sorghum (Sorghum bicolor), and (3) the intercropping of ruzigrass and sorghum. Subplots during spring prior to planting soybean were (a) pearl millet (Pennisetum glaucum), (b) sunn hemp (Crotalaria juncea), and (c) forage sorghum (Sorghum bicolor). Results: Soil C and N fractions were affected according to crop residue characteristics of the rotations. Higher soil C stocks in 2012 and 2015 (7 % an average) were observed at 0.2–0.4 m depth by ruzigrass compared to sorghum. High crop residue input with ruzigrass in the fall-winter sequestered 0.61 Mg C ha− 1 yr− 1 at 0-0.1 m soil depth compared with lower C sequestration using grain sorghum (0.29 Mg C ha− 1 yr− 1). Conclusions: The quantity and quality of crop residues impact its retention on soil surface controlling the dynamics of soil C and N fractions and can be considered relevant for soil C sequestration. These aspects could contribute to the mitigation of atmospheric CO2 in crop production systems.
Keywords: Conservation management; Crop residue quality; Cropping systems; Soil carbon stock